PERSPEKTIF AKUNTANSI MANAJEMEN LINGKUNGAN DAN PENGUNGKAPANNYA PADA NILAI PERUSAHAAN - Endiana, I Dewa Made; Suryandari, Ni Nyoman Ayu (JURNAL AKUNTANSI DAN AUDITING, 2020)
Company development does not only focus on maximum profit but also social and environmental welfare. This is in accordance with the principle of triple botton line accounting which consists of profit, planet and people. If the triple bottom line principle is not implemented, the company's environmental management is not organized, the company's environmental performance will decline and the company's desire to protect the environment is low. With environmental management accounting (EMA), companies can identify, assign and allocate costs accurately to a product or process, so that management is able to perform efficiency. EMA facilitates management in managing companies related to environmental performance management because of the availability of information starting from the use of raw materials, energy used, and water and the results of business processes such as waste. The importance of environmental performance in increasing the value of a company motivates researchers to determine whether the company's environmental performance and environmental disclosure have an effect on firm value. By using the sample selection criteria with purposive sampling, namely manufacturing companies that participated in PROPER 2016-2018, 15 companies were obtained as samples in this study. By using the PLS warp, the results show that Environmental Management Accounting has a positive effect on firm size, Environmental Management Accounting has a positive effect on Environmental Disclosure and Environmental Disclosure has a positive effect on firm size.